Johnsongrass rhizome tissue can be infected by Colletotrichum sublineola. (September 2022) - Ahn, Ezekiel; Fall, Coumba; Fan, Farrell; Prom, Louis K.; Magill, Clint
Abstract: Four isolates of Colletotrichum sublineola were inoculated on excised leaf blades and rhizomes of nine Johnsongrass accessions and leaf blades of two sorghum accessions, BTx623 (+) and SC748-5 (−). Successful acervuli formations were observed in seven Johnsongrass accession- C. sublineola isolate combinations. Although infection leading to pathogen reproduction was rarely observed, this is the first study that confirmed Johnsongrass rhizomes can be colonized by C. sublineola . Highlights: Johnsongrass rhizome tissue could be infected by Colletotrichum sublineola. Acervulus formation was rare, even in positive cultivar by isolate inoculations. Johnsongrass cultivar SH1247 was infected by all 4 isolates tested. Three Johnsongrass cultivars were positive only with one isolate.